Proceso atención de enfermería en adolescente con traumatismo de órganos intraabdominales por arma de fuego. - Ojeda Espín, Genesis Belén (2023)
This Case Study exposes a 19-year-old adolescent with chest and abdomen trauma from a firearm, who went to the emergency area of the IESS Babahoyo General Hospital, and upon admission was in critical condition, a resolution was given surgery and went to the immediate Intensive Care Unit, where his stay lasted 33 days, then he went to the hospitalization floor, developing the nursing care process within the Hospital Unit, which allowed us to provide him with the necessary care to the correction of the altered functional patterns and obtain a favorable evolution, acceding to the recovery and rehabilitation of the patient's health, resulting in his hospital discharge.